An Analysis of Psychological Resilience and Secondary Trauma Among Psychologists Involved in the Earthquake Response in Kahramanmaraş - Demirel, Burcu; Kökrek, Zekeriya (The Bulletin of Legal Medicine, 2024)
Objective: The aim of this study is to examine the relationship between the psychological resilience levels and secondary trauma levels of mental health professionals who were involved in the Kahramanmaraş-centered earthquake on February 6. Additionally, the study investigates whether psychological resilience and secondary trauma levels vary based on demographic factors. Methods: Psychological resilience has been shown to negatively predict secondary traumatic stress (β=-0.412; t=-5.034; p<0.001). It was found that having experience in similar roles and exposure to short-term traumatic events may increase psychological resilience, while working with trauma victims for extended periods may increase the risk of secondary traumatic stress Results: The findings revealed that psychological resilience negatively predicted secondary traumatic stress. Moreover, significant differences were found in the levels of psychological resilience and secondary traumatic stress according to various demographic variables. It was found that having prior experience in similar roles and being exposed to short-term traumatic events could enhance psychological resilience, while prolonged work with trauma victims could increase the risk of secondary traumatic stress. Conclusion: In conclusion, it is recommended to develop training programs and intervention strategies to enhance the psychological resilience of professionals working in disaster and trauma fields, as well as to establish institutional policies and support systems to prevent and manage secondary traumatic stress.